Sex‐specific transcriptome of spinal microglia in neuropathic pain due to peripheral nerve injury. Issue 4 (20th January 2022) - Fiore, Nathan T.; Yin, Zhuoran; Guneykaya, Dilansu; Gauthier, Christian D.; Hayes, Jessica P.; D'Hary, Aaron; Butovsky, Oleg; Moalem‐Taylor, Gila
Abstract: Neuropathic pain is a prevalent and debilitating chronic disease that is characterized by activation in glial cells in various pain‐related regions within the central nervous system. Recent studies have suggested a sexually dimorphic role of microglia in the maintenance of neuropathic pain in rodents. Here, we utilized RNA sequencing analysis and in vitro primary cultures of microglia to identify whether there is a common neuropathic microglial signature and characterize the sex differences in microglia in pain‐related regions in nerve injury and chemotherapy‐induced peripheral neuropathy mouse models. While mechanical allodynia and behavioral changes were observed in all models, transcriptomic analysis of microglia revealed no common transcriptional changes in spinal and supraspinal regions and in the different neuropathic models. However, there was a substantial change in microglial gene expression within the ipsilateral lumbar spinal cord 7 days after chronic constriction injury (CCI) of the sciatic nerve. Both sexes upregulated genes associated with inflammation, phagosome, and lysosome activation, though males revealed a prominent global transcriptional shift not observed in female mice. Transcriptomic comparison between male spinal microglia after CCI and data from other nerve injury models and neurodegenerative microglia demonstrated a unique CCI‐induced signature reflecting acute activation of microglia. Further, in vitro studies revealed that only male microglia from nerve‐injured mice developed a reactive phenotype with increased phagocytotic activity. This study demonstrates a lack of a common neuropathic microglial signature and indicates distinct sex differences in spinal microglia, suggesting they contribute to the sex‐specific pain processing following nerve injury. Main Points: No common gene signatures in microglia in neuropathic pain models. Significant changes in spinal microglia gene expression following peripheral nerve injury. Sex differences in nerve injury‐induced microglia transcriptome and phagocytic activity.